2011
DOI: 10.4172/2155-9546.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplements on Growth Performance and Phosphorus Waste Production of Australian Catfish, Tandanus Tandanus, Fed with Diets Containing Canola Meal as Fishmeal Replacement

Abstract: Effects of dietary phytase, amino acid (AA), and inorganic phosphorus (P) in canola meal diets on the growth and P waste production of Australian catfish, Tandanus tandanus were evaluated. Fishmeal protein was replaced by 30% and 45% with canola meal protein in two separate experiments, in which test diets were fortified with phytase, AA, inorganic P, or their combinations. Addition of sole phytase to the 30% replacement diets did improve growth performance and feed utilization of fish compared to those fed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The positive effects of phytase on amino acid availability have been observed in several animal studies in low phosphorus and amino acid-deficient diets [6,7,11,12,13,14]. Huynh and Nugegoda [15] reported that inclusion of phytase and/ or amino acids did not improve amino acid profile of canola meal diet supplemented with limiting amino acid in Australian catfish (Tandanus tandanus), which showed no improvement in growth of the fish. Similarly, supplementation of phytase in amino acid-adequate diet of young chicks fed diet based on groundnut cake had no effect on growth [12].…”
Section: Introductionmentioning
confidence: 99%
“…The positive effects of phytase on amino acid availability have been observed in several animal studies in low phosphorus and amino acid-deficient diets [6,7,11,12,13,14]. Huynh and Nugegoda [15] reported that inclusion of phytase and/ or amino acids did not improve amino acid profile of canola meal diet supplemented with limiting amino acid in Australian catfish (Tandanus tandanus), which showed no improvement in growth of the fish. Similarly, supplementation of phytase in amino acid-adequate diet of young chicks fed diet based on groundnut cake had no effect on growth [12].…”
Section: Introductionmentioning
confidence: 99%